Środowiska przedsiębiorczości a logika rozwoju terytorium - Chądzyński, Jacek (Entrepreneurial Environments and Logic Development of the Territory, 2007)
Current concepts of local development tend to expose the meaning of territoriality in production process and the ability of taking advantage of specific internal/endogenic resources in the defined area. One of the specifics of defined territory is local entrepreneurial environment. In the article the definitions of entrepreneurial environment from the subject literature, its most important aspects and the meaning for its territory were presented. Further, selected types of production organization forms were presented in context of its meaning in the creation and development of entrepreneurial environment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 699-707